METHODICAL APPROACH TO IDENTIFICATION AND QUANTIFICATION OF CORROSION DAMAGES OF CORROSION THE CASING STEEL TUBES IN PETROLEUM INDUSTRY - V. Aleksić (Journal of Engineering & Processing Management, 2009)
Methodological approach of identification and quantification of corrosion damages of the steel tubes which use for casing the well in petroleum industry are presented in the paper. A description and consequence of steel corrosion of casing steel tubes with examples from experience were also analyzed. Initiate steps with the aim to prevent these phenomena are considered.
Keywords: corrosion damage; casing steel tube